Material properties and failure prediction of ultrafine grained materials with bimodal grain size distribution. (January 2017) - Yadollahpour, M.; Hosseini-Toudeshky, H.
Abstract Fabrication of bimodal materials, with coarse grains embedded inside a matrix of nanocrystalline or ultrafine grains, is a key way to enhance the strength and ductility of materials. In this paper, the finite-element method is performed in conjunction with the 2D representative volume elements from the real microstructure of bimodal materials to investigate their tensile behavior. Therefore, using a composite model, a dislocation density-based constitutive equation is employed to describe the flow stress of ultrafine grain and coarse grain phases, and then, the stress–strain response of bimodal material is extracted from the mechanism-based strain gradient plasticity. Then, the proposed model combined with extended finite-element method and cohesive zone modeling is utilized to investigate the crack nucleation site and propagation path within the microstructure of the bimodal material. The predicted tensile and failure behavior are compared with available experimental results. An acceptable agreement is observed between the predicted results from the proposed model and experimental data on bimodal Ni and bimodal Al-7.5 Mg.